The European Experience: The European Convention on Human Rights - Boyle, Kevin (Victoria University of Wellington Law Review, 2009)
This article focuses on the European Convention on Human Rights and its Court of Human Rights. It explains the relationship between the Council of Europe, the Convention, and the Court as a system that is also a working example of a regional human rights mechanism. Some important rights and freedoms affirmed under the Convention are detailed, as is the impact of the Court's decisions on other judicial bodies. The article also comments on some future challenges for the Court.